2019
DOI: 10.1016/j.molstruc.2019.04.035
|View full text |Cite
|
Sign up to set email alerts
|

Mesoporous silica supported amine and amine-copper complex for CO2 adsorption: Detailed reaction mechanism of hydrophilic character and CO2 retention

Abstract: The mesoporous silica SBA-15 functionalized with various amines was prepared and then doped with copper (Cu ++). The modified materials were tested for the retention of CO 2 at room temperature using temperature-programmed desorption (CO 2-TPD). Several parameters affecting the CO 2 retention capacity (CRC) were investigated such as effect of the nature of amine groups, repetitive adsorption-desorption cycles and dispersion of copper. CO 2-TPD and H 2 O-TPD were employed in order to correlate the hydrophilic c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
17
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 40 publications
(18 citation statements)
references
References 39 publications
(68 reference statements)
1
17
0
Order By: Relevance
“…Furthermore, representative peaks for the Si2s and Si2p are also observed, attributing the presence of the silane moieties. The XPS spectrum of C1s (Figure 2b) was deconvoluted into four surface elements corresponding C-Si at 283.6 eV, sp 2 The presence of amino groups of different nature was confirmed by temperature programmed desorption of CO 2 (TPD-CO 2 ) which is a useful tool to estimate the distribution of the basic sites strength and the total basicity (Figure 1b) [20][21][22][23]. The TPD-CO 2 profile of PolyCat-Si, registered up to 150 • C to avoid any degradation of the material at higher temperature (see below thermogravimetric profile, showed two CO 2 desorption peaks, at ca.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, representative peaks for the Si2s and Si2p are also observed, attributing the presence of the silane moieties. The XPS spectrum of C1s (Figure 2b) was deconvoluted into four surface elements corresponding C-Si at 283.6 eV, sp 2 The presence of amino groups of different nature was confirmed by temperature programmed desorption of CO 2 (TPD-CO 2 ) which is a useful tool to estimate the distribution of the basic sites strength and the total basicity (Figure 1b) [20][21][22][23]. The TPD-CO 2 profile of PolyCat-Si, registered up to 150 • C to avoid any degradation of the material at higher temperature (see below thermogravimetric profile, showed two CO 2 desorption peaks, at ca.…”
Section: Resultsmentioning
confidence: 99%
“…The presence of amino groups of different nature was confirmed by temperature programmed desorption of CO 2 (TPD-CO 2 ) which is a useful tool to estimate the distribution of the basic sites strength and the total basicity ( Figure 1 b) [ 20 , 21 , 22 , 23 ]. The TPD-CO 2 profile of PolyCat-Si, registered up to 150 °C to avoid any degradation of the material at higher temperature (see below thermogravimetric profile, showed two CO 2 desorption peaks, at ca.…”
Section: Resultsmentioning
confidence: 99%
“…In the last decades, a particular interest was set on the use of the mesoporous silica in catalysis and adsorption [35][36][37][38][39][40][41][42][43][44][45][46], due to their higher specific surface areas and pore size compared to the zeolites. These catalysts may be easily recov-ered at the end of a reaction and can be reused in several cycles.…”
Section: Introductionmentioning
confidence: 99%
“…Different adsorbent materials are currently under study for the CO 2 capture process, among them are mesoporous silicas 9 . This material can be synthesized in the form of powders 10,11 , films 12,13 , fibers 14,15 and monoliths 16,17,26,27,[18][19][20][21][22][23][24][25] .…”
mentioning
confidence: 99%
“…It should be emphasized that the research on the incorporation of heteroatoms in silica-based materials has shown to be very effective in obtaining materials with high thermal stability and regenerability [31][32][33][34] . This modification technique is employed to improve, in addition to the mentioned characteristics, the properties of CO 2 adsorption 7,9,34,35 . However, it was observed that the number of scientific publications regarding the study of the evaluation of CO 2 adsorption performance for materials incorporated with heteroatoms, similar to those synthesized in this work, is extremely low 31-34 . This scarcity can be justified by the fact that the works found in the literature on the incorporation of heteroatoms do not perform this procedure with the purpose of contributing directly with the increase of the CO 2 adsorption capacity, since the materials obtained from that are not analyzed in CO 2 capture applications.…”
mentioning
confidence: 99%